Risk factors for postoperative DVT exacerbation or new DVT in patients with spinal cord injury complicated with cervical fracture - Wang, Haiying; Lv, Bing; Li, Wei; Xu, Jingjing; Ma, Ce (Frontiers in Cardiovascular Medicine, 2024)
Objective: To investigate the dynamic changes of perioperative deep venous thrombosis (DVT) in patients with spinal cord injury complicated with cervical fracture and analyze the risk factors of postoperative DVT exacerbation or new DVT.Methods: From January 2018 to December 2023, a total of 232 patients with spinal cord injury complicated with cervical fracture in our hospital were retrospectively analyzed. Ultrasonography of both lower limbs was performed before and after surgery. According to whether there was aggravation of DVT or new thrombosis, the group was divided into DVT exacerbation or new DVT group and non-DVT exacerbation group.